2009
DOI: 10.1016/j.ejso.2009.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemoradiation and pancreaticoduodenectomy for initially locally advanced head pancreatic adenocarcinoma

Abstract: BACKGROUND:The most accepted treatment for locally advanced pancreatic adenocarcinoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 30 publications
(31 reference statements)
0
21
0
1
Order By: Relevance
“…The International Study Group of Pancreatic Surgery likewise does not support neoadjuvant therapy regimens in borderline resectable pancreatic cancer (BRPC) patients with isolated venous involvement if technical options of resections are possible. 4 Nonetheless, despite a paucity of prospective data to support a standard treatment regimen for borderline resectable pancreatic cancer, neoadjuvant therapy is currently the preferred initial approach in the United States, 25,[43][44][45][46][47][48][49] and was recommended by the expert consensus statement sponsored by the AHPBA, SSAT, and SSO. 41 The rationale for pursuing preoperative treatment for patients with borderline resectable PDAC is similar to that for patients with potentially resectable pancreatic cancer, but a greater emphasis is placed on maximizing the potential for R0 resection.…”
Section: Rationale For Preoperative Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The International Study Group of Pancreatic Surgery likewise does not support neoadjuvant therapy regimens in borderline resectable pancreatic cancer (BRPC) patients with isolated venous involvement if technical options of resections are possible. 4 Nonetheless, despite a paucity of prospective data to support a standard treatment regimen for borderline resectable pancreatic cancer, neoadjuvant therapy is currently the preferred initial approach in the United States, 25,[43][44][45][46][47][48][49] and was recommended by the expert consensus statement sponsored by the AHPBA, SSAT, and SSO. 41 The rationale for pursuing preoperative treatment for patients with borderline resectable PDAC is similar to that for patients with potentially resectable pancreatic cancer, but a greater emphasis is placed on maximizing the potential for R0 resection.…”
Section: Rationale For Preoperative Therapymentioning
confidence: 99%
“…45,51 Therefore, although data are few with regard to the sequencing and duration of preoperative treatment modalities, most agree that a treatment schema that incorporates systemic chemotherapy and chemoradiation is the optimal strategy, and this notion has been embraced by several institutions and high-volume pancreatic cancer treatment centers ( Table 2). 25,[43][44][45][46][47][48][49] Metrics of Response to Neoadjuvant Therapy When neoadjuvant therapy is administered, patients should be staged before initiation and after completion of therapy (chemotherapy, chemoradiation, or both). 52,53 Changes in the patient's clinical or biologic status or the radiographic findings at the time of restaging may necessitate a reassessment of the treatment plan.…”
Section: Rationale For Preoperative Therapymentioning
confidence: 99%
“…En dehors d'une réponse tumorale évidente, l'interprétation radiologique des engainements vasculaires est complexe, l'échoendoscopie n'est pas contributive et la valeur prédictive du PET-scan n'est pas évaluée ; c'est alors l'absence d'évolutivité de la maladie, le statut clinique et la diminution, ou mieux la normalisation du taux de CA 19-9, qui conduisent à une laparotomie exploratrice. En pratique, le problème majeur est celui de l'extension artérielle et ce sont les biopsies chirurgicales des gaines artérielles qui, lorsqu'elles sont négatives, permettent d'indiquer une résection [16,17].…”
Section: Les Critères Préopératoires Théoriques D'inextirpabilité Sonunclassified
“…Even though an extreme variety of phase I/II studies [14, 15] have been published on the potential benefits for NCRT for patients with both resectable and unresectable PDAC, in addition to minimizing the possibilities of local tumor recurrence [16, 17], achieving better local tumor control [17, 18], or tumor downstaging with a subsequent potentially resectable tumor [1921], unfortunately, no randomized controlled phase III trials comparing NCRT plus surgery versus surgical treatment only have been reported up till now, and as a consequence there are certainly no evidence-based medicine proofs that NCRT can offer any benefits for patients with PDAC. Within the distinction, the entire duration of prescribed chemoradiotherapy is definitely carried out with virtually no holdoff, and it can presumptively improve usefulness for PDAC patients.…”
Section: Introductionmentioning
confidence: 99%